Co-occurrence of Campylobacter Species in Children From Eastern Ethiopia, and Their Association With Environmental Enteric Dysfunction, Diarrhea, and Host Microbiome - Terefe, Yitagele; Deblais, Loïc; Ghanem, Mostafa; Helmy, Yosra A.; Mummed, Bahar; Chen, Dehao; Singh, Nitya; Ahyong, Vida; Kalantar, Katrina; Yimer, Getnet; Yousuf Hassen, Jemal; Mohammed, Abdulmuen; et al. (Frontiers in Public Health, 2020)
High Campylobacter prevalence during early childhood has been associated with stunting and environmental enteric dysfunction (EED), especially in low resource settings. This study assessed the prevalence, diversity, abundance, and co-occurrence of Campylobacter spp. in stools from children in a rural area of eastern Ethiopia and their association with microbiome, diarrhea, and EED in children. Stool samples (n = 100) were collected from randomly selected children (age range: 360–498 days) in five kebeles in Haramaya District, Ethiopia. Diarrhea, compromised gut permeability, and gut inflammation were observed in 48, 45, and 57% of children, respectively. Campylobacter prevalence and species diversity were assessed using PCR and meta-total RNA sequencing (MeTRS). The prevalence of Campylobacter spp. in the children's stools was 50% (41–60%) by PCR and 88% (80–93.6%) by MeTRS (P < 0.01). Further, seven Campylobacter species (Campylobacter jejuni, Campylobacter upsaliensis, Campylobacter hyointestinalis, Campylobacter coli, Campylobacter sp. RM6137, uncultured Campylobacter sp., and Campylobacter sp. RM12175) were detected by MeTRS in at least 40% of children stools in high abundance (>1.76-log read per million per positive stool sample). Four clusters of Campylobacter species (5–12 species per cluster) co-occurred in the stool samples, suggesting that Campylobacter colonization of children may have occurred through multiple reservoirs or from a reservoir in which several Campylobacter species may co-inhabit. No associations between Campylobacter spp., EED, and diarrhea were detected in this cross-sectional study; however, characteristic microbiome profiles were identified based on the prevalence of Campylobacter spp., EED severity, and diarrhea. Forty-seven bacterial species were correlated with Campylobacter, and 13 of them also correlated with gut permeability, gut inflammation and/or EED severity. Forty-nine species not correlated with Campylobacter were correlated with gut permeability, gut inflammation, EED severity and/or diarrhea. This study demonstrated that (1) in addition to C. jejuni and C. coli, multiple non-thermophilic Campylobacter spp. (i.e., Campylobacter hyointestinalis, Campylobacter fetus, and Campylobacter concisus) were frequently detected in the children's stools and (2) the Campylobacter, gut permeability, gut inflammation, EED severity, and diarrhea were associated with characteristic microbiome composition. Additional spatial and longitudinal studies are needed to identify environmental reservoirs and sources of infection of children with disparate Campylobacter species and to better define their associations with EED in low-income countries.